Power-sharing in conflict-ridden societies : challenges for building peace and democratic stability /: challenges for building peace and democratic stability. (2016) - Butenschøn, Nils A (Nils August), 1949-; Stiansen, Øyvind; Vollan, Kåre
No abstract available